Low high-temperature conductivity ternary ethylene-propylene rubber material, preparation method and application thereof

CN122978602APending Publication Date: 2026-10-27CHANGLAN CABLE ACCESSORIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611090431.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明第一方面的目的,在于提供一种低高温电导率三元乙丙橡胶材料,其在90℃高温下电导率低于1.2×10-13S/m,γ90/γ23比值小于35,同时兼具优异的力学性能(抗张强度≥16.2 MPa,抗撕裂强度≥24 MPa,断裂伸长率≥621)和良好的加工性能,有效解决了现有技术中高温电导率过高、绝缘可靠性不足的问题

Benefits of technology

(1)本发明的三元乙丙橡胶材料具有低高温电导率,且高温绝缘稳定性优异。本发明通过配方与工艺的协同优化,从多个层面抑制了高温下的离子传导。具体而言,本发明采用高纯气相法白炭黑并配合硅烷偶联剂封闭表面羟基,减少了离子杂质和水分吸附;添加纳米钛酸钡等高介电常数填料,增加了材料内部的陷阱密度,有效捕获自由载流子;选用过氧化物硫化体系形成高键能的CC交联键,搭配二次硫化去除小分子副产物,使交联网络更加完善稳定。采用本发明配方制得的EPDM材料在90℃高温下的电导率低于1.2×10-13S/m,且γ90/γ23比值小于35,表明材料在高温下电导率上升幅度极小,能够有效避免电场畸变和绝缘击穿风险,满足超高压直流电缆附件对高温绝缘性能的苛刻要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a low high-temperature conductivity EPDM material and a preparation method and application thereof. The EPDM material is prepared from the following raw materials: EPDM, zinc oxide, a silane coupling agent, a nano filler modifier, fumed white carbon black, dicumyl peroxide, a vulcanization accelerator 1, a vulcanization accelerator 2, a hydrolysis-resistant and moisture-resistant agent and an auxiliary agent, wherein the hydrolysis-resistant and moisture-resistant agent comprises calcium oxide and low-molecular-weight polyethylene glycol. The synergistic optimization of the formula and the process is used to prepare the EPDM material, and the prepared EPDM material has a low high-temperature conductivity of less than 1.2*10 ‑13 S / m at 90 DEG C, a gamma 90 / gamma 23 ratio of less than 35, excellent mechanical properties and good processing performance, and can be widely applied to DC cable accessories and effectively solves the problems of high high-temperature conductivity and insufficient insulation reliability in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of EPDM rubber materials technology, and in particular to a low-temperature-conductivity EPDM rubber material, its preparation method, and its application. Background Technology

[0002] DC cable accessories are critical connecting components in ultra-high voltage direct current (UHVDC) transmission lines, and their insulation performance directly affects the safety and stability of the transmission system. Ethylene propylene diene monomer (EPDM) rubber, due to its excellent aging resistance, weather resistance, and electrical insulation properties, has become a widely used insulation material in the field of DC cable accessories. However, in actual operation, cable accessories generate heat due to current loss, leading to an increase in operating temperature. This, in turn, causes a significant increase in the high-temperature conductivity of the EPDM insulation material, resulting in uneven electric field distribution and even inducing insulation breakdown. This makes it difficult to meet the stringent high-temperature performance requirements of UHVDC transmission for insulation materials.

[0003] To address the aforementioned issues, researchers have attempted to optimize the high-temperature insulation properties of EPDM through formulation adjustments. For example, they have employed high-purity reinforcing fillers, added nanomaterials with high dielectric constants (such as barium titanate) to capture charge carriers, or used peroxide vulcanization systems to enhance the thermal stability of the cross-linked network. However, some significant shortcomings remain: on the one hand, traditional high-purity reinforcing fillers (such as silica fillers) are rich in hydroxyl groups on their surface and easily introduce metal ion impurities, which exacerbates ion conduction at high temperatures; on the other hand, modifiers such as nano-barium titanate exhibit poor dispersibility and are prone to aggregation in the EPDM matrix, leading to interfacial defects and the formation of conductive channels, thus weakening their effect on suppressing high-temperature conductivity. Furthermore, many related technologies focus on single formulation adjustments, lacking systematic synergy with the preparation process, making it difficult to simultaneously reduce high-temperature conductivity while maintaining the material's mechanical and processing properties.

[0004] Therefore, there is an urgent need to develop a preparation method that can effectively reduce the high-temperature conductivity of EPDM insulation material for DC cable accessories, so that the material maintains low conductivity at high temperatures while also possessing good mechanical strength and processing performance, in order to meet the actual requirements of ultra-high voltage DC transmission projects for the reliability of cable accessory insulation. Summary of the Invention

[0005] The first objective of this invention is to provide a low-temperature-conductivity EPDM rubber material, wherein the conductivity at 90°C is less than 1.2 × 10⁻⁶. -13 S / m, γ 90 / γ 23 With a ratio of less than 35, it also possesses excellent mechanical properties (tensile strength ≥16.2 MPa, tear strength ≥24 MPa, elongation at break ≥621) and good processing performance, effectively solving the problems of excessively high high-temperature conductivity and insufficient insulation reliability in existing technologies.

[0006] The second objective of this invention is to provide a method for preparing a low-temperature-conductivity EPDM rubber material.

[0007] The third aspect of this invention aims to provide the application of the above-mentioned low-temperature conductivity EPDM rubber material or the low-temperature conductivity EPDM rubber material prepared by the above-mentioned preparation method in the preparation of DC cable accessories.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a low-temperature-conductivity EPDM rubber material, wherein the raw materials for its preparation, by weight, comprise: 80-120 parts of EPDM rubber; 3-5 parts zinc oxide; 2-4 parts of silane coupling agent; 1-3 parts of nanofiller modifier; 30-45 parts of fumed silica 2-3 parts of dicumyl peroxide; 11-1.5 parts of vulcanization accelerator; Vulcanization accelerator: 20.3~0.8 parts; 2-5 parts of anti-hydrolysis and anti-hygroscopic agent; Additives: 11.5~23.5 parts; The vulcanization accelerator 1 includes at least one of triallyl isocyanurate and triallyl cyanurate; the vulcanization accelerator 2 includes at least one of sulfur and tetramethyldithiuram; and the anti-hydrolysis and anti-hygroscopic agent includes calcium oxide and low molecular weight polyethylene glycol.

[0009] The EPDM rubber material according to embodiments of the present invention has at least the following beneficial effects: (1) The EPDM rubber material of the present invention has low high-temperature conductivity and excellent high-temperature insulation stability. The present invention suppresses ion conduction at high temperatures from multiple levels through synergistic optimization of formulation and process. Specifically, the present invention uses high-purity fumed silica and silane coupling agent to block surface hydroxyl groups, reducing ion impurities and moisture adsorption; adds high dielectric constant fillers such as nano-barium titanate, increasing the trap density inside the material and effectively capturing free carriers; and selects a peroxide vulcanization system to form high bond energy C C-linking bonds, combined with secondary sulfurization to remove small molecule byproducts, result in a more complete and stable crosslinking network. The EPDM material prepared using the formulation of this invention exhibits an electrical conductivity of less than 1.2 × 10⁻⁶ at 90°C. -13 S / m, and γ 90 / γ 23A ratio of less than 35 indicates that the material's conductivity increases very little at high temperatures, effectively avoiding the risk of electric field distortion and insulation breakdown, and meeting the stringent requirements of ultra-high voltage DC cable accessories for high-temperature insulation performance.

[0010] (2) The EPDM rubber material of the present invention combines mechanical strength, flexibility, and processing performance. The EPDM rubber material of the present invention reduces high-temperature electrical conductivity while possessing excellent mechanical properties. Test results show that the EPDM rubber material prepared using the formulation of the present invention has a tensile strength ≥16.2 MPa, a tear strength ≥24 MPa, an elongation at break ≥621, and a crosslinking density higher than 1.2 × 10⁻⁶. -4 mol / cm 3 The Mooney viscosity (90°C) is less than 50, indicating that the material prepared by this invention has sufficient mechanical strength to withstand the mechanical stress during the installation and operation of cable accessories, while also having good flexibility and processing fluidity, which facilitates subsequent processes such as mixing and vulcanization, and will not become brittle or difficult to process due to excessive filler or excessive cross-linking.

[0011] In some embodiments of the present invention, the EPDM rubber contains 4-6 wt% ethylene-bis(norbornene) as the third monomer, 68-75 wt% ethylene, and has a Mooney viscosity (ML(1+4)) of 45-60 at 100°C.

[0012] EPDM rubber with ethylene-propylene-diene monomer (ENB) as the third monomer is selected. The ENB content is controlled at 4-6 wt%, which can ensure vulcanization activity and avoid the increase of polar groups caused by excessive ENB content, thus reducing ion dissociation at high temperature. The ethylene content is controlled at 68-75 wt%, which can improve the crystallinity and molecular density of the rubber and hinder ion migration. The Mooney viscosity ML(1+4) at 100℃ is 45-60, which can balance processing fluidity and mechanical strength. It avoids uneven filler dispersion due to excessive viscosity, or insufficient shear force due to low friction during mixing due to excessively low viscosity, which affects filler dispersion.

[0013] In some embodiments of the present invention, the zinc oxide is high-purity indirect-method active zinc oxide with a purity ≥99.5%.

[0014] In some embodiments of the present invention, the particle size of the zinc oxide is 1~100 nm.

[0015] In some embodiments of the present invention, the silane coupling agent includes at least one of bis-[γ-(triethoxysilane)propyl]tetrasulfide (i.e., silane coupling agent Si-69), KH-560, and KH-792.

[0016] Silane coupling agents can chemically react with the Si-OH hydroxyl groups on the surface of silica to block the hydroxyl groups, thus changing the silica from hydrophilic to hydrophobic, reducing water adsorption and ion dissociation. At the same time, they can improve the compatibility of silica with EPDM, optimize interfacial bonding, and block interfacial ion migration channels.

[0017] In some embodiments of the present invention, the nanofiller modifier includes at least one of nano barium titanate, nano strontium titanate, or nano barium strontium titanate.

[0018] Nanofiller modifiers are high dielectric constant materials such as nano barium titanate, strontium titanate, and barium strontium titanate. They can increase the trap density and trap depth of the material, inhibit space charge accumulation and ion migration, but excessive addition will lead to a decrease in insulation performance.

[0019] In some embodiments of the present invention, the particle size of the nanofiller modifier is 100~800nm.

[0020] In some embodiments of the present invention, the purity of the fumed silica is ≥99.8%.

[0021] In some embodiments of the present invention, the specific surface area of ​​the fumed silica is 150~250 m². 2 / g. If the specific surface area is too high, it will easily absorb water and agglomerate; if it is too low, the reinforcing effect will be insufficient.

[0022] In some embodiments of the present invention, Na in the fumed silica + Fe 3+ Al 3+ Impurity content <5ppm.

[0023] Low levels of metal ion impurities can reduce the source of ion carriers at high temperatures.

[0024] In some embodiments of the present invention, the calcium oxide is 1 to 3 parts by weight, and the low molecular weight polyethylene glycol is 0.5 to 1 part.

[0025] In some embodiments of the present invention, the purity of the calcium oxide is ≥98%.

[0026] In some embodiments of the present invention, the relative molecular weight of the low molecular weight polyethylene glycol is 500-800, preferably 600.

[0027] In some embodiments of the present invention, the additives include at least one of stearic acid, antioxidants, and plasticizers.

[0028] In some embodiments of the present invention, the additives include 0.5 to 1.5 parts stearic acid, 1 to 2 parts antioxidant, and 10 to 20 parts plasticizer by weight.

[0029] In some embodiments of the present invention, the plasticizer comprises paraffin oil, wherein the aromatic hydrocarbon content of the paraffin oil is <5%.

[0030] The plasticizer used in this invention is paraffin oil (aromatic content <5%), which, compared to ester and ether plasticizers, helps to avoid the generation of ions through high-temperature hydrolysis.

[0031] In some embodiments of the present invention, the antioxidant includes at least one of antioxidant 4010NA, antioxidant MB, and antioxidant RD.

[0032] A second aspect of the present invention provides a method for preparing a low-temperature-conductivity EPDM rubber material as described in the first aspect, comprising the following steps: S1. The EPDM rubber is plasticized and broken down, and then the nanofiller modifier, zinc oxide, fumed silica, additives, silane coupling agent and anti-hydrolysis and anti-hygroscopic agent are added respectively, and the mixture is mixed to obtain a mixed rubber compound. S2. After the mixed rubber compound is milled and cooled, it undergoes a first thin-pass treatment, then dicumyl peroxide, vulcanization accelerator 1 and vulcanization accelerator 2 are added, followed by a second thin-pass treatment, and then vulcanization treatment and secondary vulcanization treatment are performed in sequence to obtain the final product.

[0033] The preparation method according to embodiments of the present invention has at least the following beneficial effects: The preparation method of the present invention is simple and low in cost. The raw materials used are all commonly used industrial materials (such as fumed silica, diisopropylbenzene peroxide, paraffin oil, etc.), and no expensive special reagents are required.

[0034] In some embodiments of the present invention, in step S1, the plasticizing and breaking time is 5-10 minutes and the temperature is 110-120°C.

[0035] In some embodiments of the present invention, step S1, the method for preparing the mixed adhesive specifically includes: S11. The nanofiller modifier, zinc oxide, fumed silica and plasticizer are added sequentially to the broken EPDM rubber and mixed to obtain nano masterbatch; S12. Stearic acid, antioxidant, silane coupling agent, calcium oxide and low molecular weight polyethylene glycol are added to the nano-masterbatch, and the mixture is then mixed twice to obtain the final product.

[0036] In some embodiments of the present invention, in step S11, the temperature of the secondary mixing is 120~130°C.

[0037] In some embodiments of the present invention, in step S11, the discharge temperature after secondary mixing is <135°C.

[0038] In some embodiments of the present invention, in step S2, the temperature of the open mill is 170~190°C.

[0039] In some embodiments of the present invention, in step S2, the refining time is 5 to 10 minutes.

[0040] In some embodiments of the present invention, in step S2, the temperature after cooling is 23±2℃.

[0041] In some embodiments of the present invention, step S2 further includes a period of rest after cooling, the resting time being 16 to 24 hours.

[0042] In some embodiments of the present invention, in step S2, the first thin-pass treatment is performed 8 to 10 times.

[0043] In some embodiments of the present invention, in step S2, the second thin-pass treatment is performed 8 to 10 times.

[0044] In some embodiments of the present invention, in step S2, the vulcanization treatment is carried out at a temperature of 160-170°C, a pressure of 12-15 MPa, and a vulcanization time of 18-24 min.

[0045] In some embodiments of the present invention, in step S2, the temperature of the secondary vulcanization treatment is 145~155℃, and the vulcanization time is 2~4h.

[0046] In some embodiments of the present invention, in step S2, the temperature of the secondary vulcanization treatment is 148~152℃, and the vulcanization time is 2~4h.

[0047] This invention employs a secondary vulcanization process. On one hand, it can fully decompose and volatilize residual peroxide decomposition products (such as small molecule polar substances like acetophenone and cumyl alcohol), preventing these byproducts from ionizing at high temperatures to generate additional ion carriers, thereby effectively suppressing the increase in high-temperature conductivity. On the other hand, secondary vulcanization can further complete the cross-linking reaction of insufficiently cross-linked molecular chains, increase the cross-linking density and improve the cross-linking network structure, making the cross-linking bonds more stable and the free volume smaller at high temperatures, thus increasing the resistance to ion migration.

[0048] In some embodiments of the present invention, in step S2, the heating rate of the secondary vulcanization treatment is 4~6℃ / min, and the cooling rate is 2~4℃ / min.

[0049] A third aspect of the present invention provides the application of the low-temperature conductivity EPDM rubber material as described in the first aspect or the low-temperature conductivity EPDM rubber material prepared by the preparation method described in the second aspect in the preparation of DC cable accessories.

[0050] Other features and advantages of the present invention will be set forth in the following description. Detailed Implementation

[0051] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0052] The terms "preferred," "more preferably," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.

[0053] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0054] In the description of this invention, the reference term "and / or" includes all and any combination of one or more of the associated listed items. For example, A and / or B includes (A and B) and (A or B).

[0055] Unless otherwise specified, the Lanxess 2470E EPDM rubber used in this embodiment has an ethylene content of 69wt%, an ENB content of 4.2wt%, and a Mooney viscosity ML(1+4) of 50 at 100°C.

[0056] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0057] Example 1 This embodiment provides a low-temperature-conductivity EPDM rubber material and its preparation method, wherein the raw materials for preparing the low-temperature-conductivity EPDM rubber material include, by weight parts: 100 parts of Lanxess 2470E EPDM rubber; 4 parts of active zinc oxide; 1 part stearic acid; Anti-aging agent 4010NA 1.5 parts; 15 parts of paraffin oil (aromatic content 3%); 40 parts of fumed silica; 92 parts of silane coupling agent Si-6; Two parts of nano-barium titanate; 2.5 parts of dicumyl peroxide (DCP); 1.2 parts triallyl isocyanurate (TAIC); 0.5 parts sulfur; 2.5 parts calcium oxide; 0.75 parts of low molecular weight polyethylene glycol (PEG600).

[0058] In this example, the Lanxess 2470E EPDM rubber used has an ethylene content of 69 wt%, an ENB content of 4.2 wt%, and a Mooney viscosity (ML(1+4)) of 50 at 100°C. The activated zinc oxide was purchased from Dalian Jinshi Zinc Oxide Co., Ltd., with a purity of 99.8%; the fumed silica has a specific surface area of ​​200 m² / g. 2 / g, Na + The content is approximately 3 ppm; the CAS number of the silane coupling agent Si-69 is 40372-72-3; the particle size of the nano barium titanate is approximately 400 nm.

[0059] The preparation method of the above-mentioned low-temperature-conductivity EPDM rubber material includes the following steps: (1) Raw material pretreatment: Fumed silica, nano-barium titanate, calcium oxide, and low molecular weight polyethylene glycol were placed in a vacuum drying oven and dried at 100°C for 2 hours for later use.

[0060] Drying helps remove adsorbed physical moisture and volatile impurities from the surface of the powder raw materials, preventing moisture from ionizing and generating H+ during subsequent high-temperature processing. + and OH - This process generates free ion carriers, thereby suppressing the rise in high-temperature ionic conductivity at the source. Simultaneously, drying improves the dispersibility of the nanofiller and reduces agglomeration caused by moisture.

[0061] (2) Plasticizing and breaking down: According to the above weight proportions, weigh out ethylene propylene diene monomer (EPDM) rubber and put it into a pressure mixer. Set the mixer temperature to 115℃ and the rotor speed to 40 r / min, and carry out plasticizing and breaking down treatment for 8 minutes to obtain EPDM rubber compound.

[0062] The plasticizing process causes the EPDM molecular chains to break down to a moderate degree through mechanical shearing, reducing its Mooney viscosity and improving the fluidity and plasticity of the compound, thus laying the foundation for the uniform dispersion of subsequent fillers.

[0063] (3) Preparation of masterbatch: First, nano-barium titanate is added to the EPDM compound after it has been broken down, and the mixture is kneaded for 4 minutes to prepare the first nano-masterbatch. Adding nano-barium titanate first allows the high dielectric constant nanoparticles to initially embed into the rubber matrix, using shear force to break down the aggregates and achieve primary dispersion.

[0064] Then, high-purity active zinc oxide is added to the first nano-masterbatch and mixed for 4 minutes to prepare the second nano-masterbatch. Zinc oxide, acting as a vulcanization activator, is added at this stage to help it disperse evenly. Simultaneously, the nanoparticle size of zinc oxide can further fill the free volume between rubber molecules, hindering ion migration.

[0065] Finally, fumed silica and paraffin oil were added to the second nano-masterbatch and mixed for 10 minutes to prepare the third nano-masterbatch. Fumed silica, as the main reinforcing filler, needs to be fully mixed to ensure its uniform distribution in the matrix; while paraffin oil, as a plasticizer, can reduce the viscosity of the rubber compound and promote filler dispersion, while its low aromatic content avoids the introduction of polar ionic impurities.

[0066] (4) Secondary mixing: According to the above weight proportions, stearic acid, antioxidant 4010NA, silane coupling agent Si-69, calcium oxide and low molecular weight polyethylene glycol were added to the above third nano masterbatch. The internal mixer temperature was controlled at 125°C, the speed at 40 r / min, and the mixing was carried out for 7 min. The discharge temperature was 130°C to obtain the mixed rubber compound.

[0067] During this stage, the silane coupling agent Si-69 chemically reacts with the silanol groups on the surface of silica, blocking the hydroxyl groups and converting the silica from hydrophilic to hydrophobic, thus reducing moisture adsorption and ion dissociation. Simultaneously, calcium oxide and polyethylene glycol work synergistically; calcium oxide chemically adsorbs trace amounts of moisture, while polyethylene glycol blocks residual silanol groups through hydrogen bonds, further inhibiting high-temperature ion conduction. The debinding temperature should not exceed 135℃ to avoid premature decomposition and inactivation of the coupling agent.

[0068] (5) Heat treatment and storage: The above-mentioned mixed rubber compound was transferred to a two-roll mill and subjected to high-temperature heat treatment at 180°C for 8 minutes. Then the rubber compound was naturally cooled to 23±2°C and left to stand in a constant temperature and humidity environment for 20 hours for later use.

[0069] Heat treatment can promote the volatilization of residual small molecules in the rubber compound (such as unreacted coupling agents, moisture, oligomers, etc.) and reduce the content of ionizable substances at high temperatures; at the same time, it helps the reaction between silane coupling agents and silica to be more complete.

[0070] (6) Vulcanization treatment: The cooled rubber compound was placed in a two-roll mill, and the mill roll temperature was controlled at 75°C. A first thin pass of 9 times was performed to ensure that the rubber compound had a uniform texture and thickness. Then, dicumyl peroxide (DCP), triallyl isocyanurate (TAIC), and sulfur were added, and a second thin pass of 9 times was performed to ensure that the vulcanization system was completely dispersed in the rubber compound.

[0071] The uniformly mixed rubber compound is placed into a flat vulcanizing machine. The vulcanization temperature is set to 165℃, the pressure to 13 MPa, and the vulcanization time to the positive vulcanization time t. 90 (Tested to be 18 minutes) Add another 4 minutes, for a total vulcanization time of 22 minutes.

[0072] (7) Secondary vulcanization: After the above vulcanization is completed, the rubber compound is cooled to room temperature and placed in a forced-air drying oven. The temperature is slowly increased to 150°C at a rate of 5°C / min. The compound is then vulcanized in hot air at this temperature for 3 hours. Finally, it is cooled to room temperature at a rate of 3°C / min to obtain the target product.

[0073] The post-vulcanization step helps to decompose residual peroxide decomposition products (such as small molecules like acetophenone and cumyl alcohol), causing them to volatilize and escape, thus preventing these polar substances from ionizing and generating ion carriers at high temperatures. At the same time, it helps to further complete the cross-linking reaction of insufficiently cross-linked molecular chains, improving the cross-linking density and the stability of the cross-linking network.

[0074] Example 2 This embodiment provides a low-temperature conductivity EPDM rubber material and its preparation method, which differs from Embodiment 1 in that the raw materials used in its preparation are different.

[0075] The raw materials for preparing this low-temperature-conductivity EPDM rubber material, by weight, include: 100 parts of Lanxess 2470E EPDM rubber; 3 parts of active zinc oxide; Stearic acid 0.5 parts; Anti-aging agent RD 1 part; 10 parts of paraffin oil (4% aromatic content); 30 parts of fumed silica; 2 parts of silane coupling agent KH-560; 1 part of nano-strontium titanate; 2.0 parts of dicumyl peroxide (DCP); 1.0 part of triallyl cyanurate (TAC); 0.3 parts of tetramethylthiuram dithiocarbamate; 2 parts calcium oxide; 0.5 parts of low molecular weight polyethylene glycol (PEG600).

[0076] In this example, the Lanxess 2470E EPDM rubber used has an ethylene content of 69 wt%, an ENB content of 4.2 wt%, and a Mooney viscosity (ML(1+4)) of 50 at 100°C. The purity of the active zinc oxide is 99.5%; the specific surface area of ​​the fumed silica is 150 m² / s. 2 / g, Na + The content is approximately 4 ppm; the particle size of nano-strontium titanate is approximately 600 nm.

[0077] The above-mentioned low-temperature conductivity EPDM rubber material was prepared according to the method in Example 1, wherein triallyl isocyanurate and sulfur were replaced with triallyl cyanurate and tetramethyldithiothiuram.

[0078] Example 3 This embodiment provides a low-temperature conductivity EPDM rubber material and its preparation method, which differs from Embodiment 1 in that the raw materials used in its preparation are different.

[0079] The raw materials for preparing this low-temperature-conductivity EPDM rubber material, by weight, include: 100 parts of Lanxess 2470E EPDM rubber; 5 parts of high-purity indirect-method activated zinc oxide; 1.5 parts stearic acid; Anti-aging agent MB 2 parts; Paraffin oil (aromatic content 2%) 20 parts; 45 parts of fumed silica; 24 parts of silane coupling agent KH-79; Three parts of nano-strontium barium titanate; 3.0 parts of dicumyl peroxide (DCP); 1.5 parts triallyl isocyanurate (TAIC); 0.8 parts sulfur; 3 parts calcium oxide; 1.0 part of low molecular weight polyethylene glycol (PEG600).

[0080] In this example, the Lanxess 2470E EPDM rubber used has an ethylene content of 69 wt%, an ENB content of 4.2 wt%, and a Mooney viscosity (ML(1+4)) of 50 at 100°C. The purity of the active zinc oxide is 99.8%; the specific surface area of ​​the fumed silica is 250 m² / g. 2 / g, Na + The content is approximately 2 ppm; the particle size of nano-strontium barium titanate is approximately 500 nm.

[0081] The preparation method of the above-mentioned low-temperature-conductivity EPDM rubber material is the same as that in Example 1. Comparative Example 1 This comparative example provides a ternary ethylene propylene diene monomer (EPDM) rubber material and its preparation method. The difference between this and Example 1 is that precipitated silica (97% purity, specific surface area 180 m²) is used. 2 / g) replaces fumed silica, without the addition of silane coupling agents. Everything else is the same.

[0082] The preparation method of the above-mentioned EPDM rubber material is described in Example 1.

[0083] Comparative Example 2 This comparative example provides a EPDM rubber material and its preparation method, which uses the same raw materials as in Example 1, but does not involve a secondary vulcanization step, and the vulcanization time is t. 90 (18 min). The rest are the same.

[0084] Comparative Example 3 This comparative example provides a EPDM rubber material and its preparation method, which differs from Example 1 in that the vulcanizing agent system is different.

[0085] The raw materials for preparing the EPDM rubber material, by weight, include: 100 parts of Lanxess 2470E EPDM rubber; 4 parts of active zinc oxide; 1 part stearic acid; Anti-aging agent 4010NA 1.5 parts; 15 parts of paraffin oil (aromatic content 3%); 40 parts of fumed silica; 92 parts of silane coupling agent Si-6; Two parts of nano-barium titanate; Accelerator M1.2 parts; Sulfur 3 parts; 2.5 parts calcium oxide; 0.75 parts of low molecular weight polyethylene glycol (PEG600).

[0086] Accelerator M was purchased from Shandong Shangshun Chemical Co., Ltd.

[0087] The preparation method of the above-mentioned EPDM rubber material is described in Example 1.

[0088] Comparative Example 4 This comparative example provides a ternary ethylene propylene diene monomer (EPDM) rubber material and its preparation method. The difference between this material and Example 1 is that nano-barium titanate is not added, while the rest are the same.

[0089] The preparation method of the above-mentioned EPDM rubber material is described in Example 1.

[0090] Comparative Example 5 This comparative example provides a EPDM rubber material and its preparation method, which differs from Example 1 in that the amount of silica filler is 50 parts, while the rest are the same.

[0091] The preparation method of the above-mentioned EPDM rubber material is described in Example 1.

[0092] Comparative Example 6 This comparative example provides a EPDM rubber material and its preparation method, which differs from Example 1 in that: low molecular weight polyethylene glycol is not added to the formulation, but the rest are the same.

[0093] The preparation method of the above-mentioned EPDM rubber material is described in Example 1.

[0094] Comparative Example 7 This comparative example provides a EPDM rubber material and its preparation method, which differs from Example 1 in that calcium oxide is not added to the formulation, but the rest are the same.

[0095] The preparation method of the above-mentioned EPDM rubber material is described in Example 1.

[0096] Test Example 1: Mechanical Performance Related Tests In this example, the crosslinking density, mechanical properties, Mooney viscosity, and trace water content of the EPDM rubber materials prepared in Examples 1-3 and Comparative Examples 1-7 were determined.

[0097] Please refer to Table 1 for the measurement results.

[0098] Table 1

[0099] The test results show that the EPDM rubber material prepared using the raw materials and process of the present invention has excellent mechanical properties, including tensile strength ≥16.2 MPa, tear strength ≥24 MPa, elongation at break ≥621, high crosslinking density, moderate Mooney viscosity, low water content, and excellent processing performance.

[0100] Compared to Example 1, Comparative Example 1 used precipitated silica without the addition of silane coupling agent. The results showed a significant decrease in crosslinking density and a deterioration in mechanical properties. This may be related to the low purity of the precipitated silica, the presence of numerous metal ion impurities, and the fact that the surface hydroxyl groups were not blocked by the silane coupling agent. Impurity ions tend to exacerbate ion conduction at high temperatures. Furthermore, the poor compatibility between silica and EPDM leads to increased interfacial defects, thus affecting mechanical properties. In addition, Comparative Example 3 used a different sulfur vulcanization system (without DCP / TAIC). The results showed a significant decrease in crosslinking density and mechanical properties (such as tensile strength and elongation at break). This may be related to the fact that the polysulfide bonds (bond energy ~260 kJ / mol) formed during sulfur vulcanization are easily broken at high temperatures, generating ionic byproducts.

[0101] Compared with Example 1, Comparative Example 2 did not undergo secondary vulcanization during the preparation process. Although the crosslinking density and mechanical properties did not change significantly, the micro-water content of the obtained EPDM rubber material was presumably due to the lack of post-vulcanization, which resulted in the incomplete vulcanization of residual peroxide decomposition products (such as acetophenone, cumyl alcohol, and other small molecule polar substances). These substances ionize at high temperatures to generate additional ion carriers. At the same time, due to the poor integrity of the crosslinking network, the free volume inside the material is large, which ultimately leads to a significant increase in micro-water content. It is worth noting that a higher micro-water content is not conducive to reducing high-temperature conductivity.

[0102] Compared to Example 1, Comparative Examples 4, 6, and 7 omitted barium titanate nanoparticles, low molecular weight polyethylene glycol, and calcium oxide, respectively. When barium titanate nanoparticles were omitted, the crosslinking density, mechanical properties, and trace water content of the materials were comparable to those of Example 1. However, when low molecular weight polyethylene glycol was omitted, the trace water content of the resulting materials increased significantly. This is presumably because, under normal conditions, polyethylene glycol seals the residual silanol groups on the surface of silica that are not completely capped by the silane coupling agent through hydrogen bonds. However, without polyethylene glycol, these hydrophilic hydroxyl groups are exposed, absorbing a large amount of moisture from the air, ultimately leading to a significant increase in trace water content. The same applies when calcium oxide is omitted. Calcium oxide, as a chemical desiccant, can react with trace amounts of water to form calcium hydroxide, irreversibly fixing moisture. When calcium oxide is absent, moisture in the rubber compound cannot be effectively adsorbed, resulting in a significant increase in trace water content. This indicates that the synergistic combination of calcium oxide and polyethylene glycol can effectively reduce the trace water content of EPDM rubber materials, thereby helping to reduce high-temperature conductivity.

[0103] Experimental Example 2: High-Temperature Conductivity Testing In this example, the high-temperature electrical conductivity properties of the EPDM rubber materials prepared in Examples 1-3 and Comparative Examples 1-7 were determined. The test method refers to the standard GB / T 1692-2008 Determination of Insulation Resistivity of Vulcanized Rubber.

[0104] Please refer to Table 2 for the measurement results.

[0105] Table 2

[0106] Note: γ in the table 90 The γ represents the electrical conductivity (S / m) of EPDM rubber at 90℃, simulating the electrical performance of DC cable accessories under high-temperature operating conditions; 23 The electrical conductivity (S / m) of the representative material at 23℃ is used as the reference value at room temperature; γ 90 / γ 23 Used to evaluate high-temperature stability, the smaller the ratio, the more gradual the increase in electrical conductivity of the material at high temperatures, that is, the better the high-temperature insulation stability, and vice versa.

[0107] The above-mentioned high-temperature conductivity test results show that the EPDM rubber materials prepared using Examples 1-3 of this invention all have a conductivity of 3.4 × 10⁻⁶ at room temperature (23℃). -15 ~3.9×10 -15 The conductivity is extremely low, with a value of only 9.1 × 10⁻⁶ S / m at high temperatures (90°C). -14 ~1.1×10 -13 S / m, and γ 90 / γ 23 The ratios are all less than 35 (the lowest being 23.33), indicating that the present invention effectively suppresses high-temperature ion conduction through the synergy of formulation and process, reduces the increase in conductivity of the material at high temperatures, and the resulting material has excellent high-temperature insulation stability.

[0108] Compared to Example 1, the conductivity at 90°C of Comparative Example 1 increased to 2.5 × 10⁻⁶. -13 S / m, γ 90 / γ 23 The conductivity reached 59.52, which may be related to the low purity of the silica, the high amount of metal ion impurities, and the lack of sealing of surface hydroxyl groups. At high temperatures, the dissociation of ionic impurities intensifies, and the poor compatibility between silica and the matrix easily leads to interface defects, affecting high-temperature conductivity. Comparative Example 2, without secondary sulfurization treatment, showed a conductivity of 1.9 × 10⁻⁶ at 90℃. -13 S / m, γ 90 / γ 23 The conductivity was 52.77, which may be related to the fact that residual DCP decomposition products (such as acetophenone and cumyl alcohol) in the system did not volatilize. These products ionize at high temperatures, generating additional charge carriers and affecting the high-temperature conductivity. Comparative Example 3 used a sulfur sulfidation system. Due to the low bond energy of polysulfide bonds, they are easily broken at high temperatures, producing ionic byproducts. Simultaneously, the crosslinking density decreased, resulting in low ion migration resistance, ultimately leading to a conductivity as high as 1.0 × 10⁻⁶ at 23°C. -13 S / m (nearly 30 times higher than in Example 1), conductivity at 90°C increased to 9.8 × 10⁻⁶. -12 S / m, γ 90 / γ23 The temperature drops to 98, indicating a significant decrease in high-temperature insulation performance.

[0109] Compared to Example 1, Comparative Examples 4, 6, and 7 omitted barium titanate nanoparticles, low molecular weight polyethylene glycol, and calcium oxide, respectively. When barium titanate nanoparticles were omitted, the conductivity at 90°C increased to 2.3 × 10⁻⁶. -13 The S / m ratio is likely due to the lack of trapping sites provided by high dielectric constant nanofillers, which fails to effectively capture free charge carriers, leading to intensified ion migration. When low molecular weight polyethylene glycol or calcium oxide is absent, the conductivity at 90℃ significantly increases, presumably related to the large number of ion carriers generated by water ionization at high temperatures.

[0110] In summary, this invention provides a low-temperature-conductivity EPDM rubber material, its preparation method, and its applications. Specifically, this invention significantly reduces ion conductivity at high temperatures by optimizing the raw materials and processes. Specifically, in terms of raw materials, this invention uses high-purity fumed silica combined with a silane coupling agent to block hydroxyl groups. High-dielectric-constant fillers such as nano-barium titanate are added to increase trap density. A peroxide vulcanization system (DCP combined with TAIC) is selected to form high-bond-energy CC crosslinks. Calcium oxide and polyethylene glycol are introduced as anti-hydrolysis and anti-hygroscopic agents, achieving dual protection of "water fixation + hydroxyl group blocking". Furthermore, in terms of the preparation process, this invention ensures uniform dispersion of fillers and removes small-molecule byproducts through stepwise masterbatch mixing, high-temperature heat treatment, optimized vulcanization, and secondary post-vulcanization. The EPDM rubber material prepared using the formulation and process of this invention has a conductivity of less than 1.2 × 10⁻⁶ at 90℃. -13 S / m, γ 90 / γ 23 With a ratio of less than 35, it also possesses excellent mechanical properties (tensile strength ≥16.2 MPa, tear strength ≥24 MPa, elongation at break ≥621) and good processing performance, effectively solving the problems of excessively high high-temperature conductivity and insufficient insulation reliability in existing technologies, and meeting the stringent requirements of ultra-high voltage DC cable accessories for insulation materials.

[0111] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A low-temperature-conductivity EPDM rubber material, characterized in that, The raw materials for preparation, by weight, include: 80-120 parts of EPDM rubber; 3-5 parts zinc oxide; 2-4 parts of silane coupling agent; 1-3 parts of nanofiller modifier; 30-45 parts of fumed silica 2-3 parts of dicumyl peroxide; 11-1.5 parts of vulcanization accelerator; Vulcanization accelerator: 20.3~0.8 parts; 2-5 parts of anti-hydrolysis and anti-hygroscopic agent; Additives: 11.5~23.5 parts; The vulcanization accelerator 1 includes at least one of triallyl isocyanurate and triallyl cyanurate; the vulcanization accelerator 2 includes at least one of sulfur and tetramethyldithiuram; and the anti-hydrolysis and anti-hygroscopic agent includes calcium oxide and low molecular weight polyethylene glycol.

2. The low-temperature-conductivity EPDM rubber material according to claim 1, characterized in that, In the EPDM rubber, the content of the third monomer, ethylene norbornene, is 4-6 wt%, the ethylene content is 68-75 wt%, and the Mooney viscosity ML(1+4) at 100°C is 45-60.

3. The low-temperature-conductivity EPDM rubber material according to claim 1, characterized in that, The zinc oxide is high-purity indirect-method active zinc oxide with a purity ≥99.5% and a particle size of 1~100nm; And / or, the silane coupling agent includes at least one of bis-[γ-(triethoxysilane)propyl]tetrasulfide, KH-560, and KH-792; And / or, the nanofiller modifier includes at least one of nano barium titanate, nano strontium titanate, or nano barium strontium titanate; And / or, the fumed silica has a purity ≥99.8% and a specific surface area of ​​150~250 m². 2 / g.

4. The low-temperature-conductivity EPDM rubber material according to claim 1, characterized in that, The calcium oxide is 1 to 3 parts by weight, and the low molecular weight polyethylene glycol is 0.5 to 1 part. And / or, the relative molecular weight of the low molecular weight polyethylene glycol is 500-800.

5. The low-temperature-conductivity EPDM rubber material according to any one of claims 1 to 4, characterized in that, The additives include at least one of stearic acid, antioxidants, and plasticizers.

6. The low-temperature-conductivity EPDM rubber material according to claim 5, characterized in that, The additives, by weight, include 0.5 to 1.5 parts stearic acid, 1 to 2 parts antioxidant, and 10 to 20 parts plasticizer; And / or, the plasticizer comprises paraffin oil, wherein the aromatic hydrocarbon content of the paraffin oil is <5%; And / or, the antioxidant includes at least one of antioxidant 4010NA, antioxidant MB, and antioxidant RD.

7. A method for preparing a low-temperature-conductivity EPDM rubber material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. The EPDM rubber is plasticized and broken down, and then the nanofiller modifier, zinc oxide, fumed silica, additives, silane coupling agent and anti-hydrolysis and anti-hygroscopic agent are added respectively, and the mixture is mixed to obtain a mixed rubber compound. S2. After the mixed rubber compound is milled and cooled, after the first thin pass treatment, the dicumyl peroxide, the vulcanization accelerator 1 and the vulcanization accelerator 2 are added, and then a second thin pass treatment is performed. Then, vulcanization treatment and secondary vulcanization treatment are performed in sequence to obtain the final product.

8. The preparation method according to claim 7, characterized in that, In step S1, the preparation method of the mixed rubber compound specifically includes: S11. The nanofiller modifier, zinc oxide, fumed silica and plasticizer are added sequentially to the broken EPDM rubber and mixed to obtain nano masterbatch; S12. Stearic acid, antioxidant, silane coupling agent, calcium oxide and low molecular weight polyethylene glycol are added to the nano-masterbatch, and the mixture is then mixed twice to obtain the final product.

9. The preparation method according to claim 7, characterized in that, In step S2, the temperature of the open mill is 170~190℃ and the time is 5~10min; And / or, the vulcanization treatment is carried out at a temperature of 160~170℃, a pressure of 12~15MPa, and a vulcanization time of 18~24min; And / or, the temperature of the secondary vulcanization treatment is 145~155℃, and the vulcanization time is 2~4h.

10. The application of the low-temperature conductivity EPDM rubber material as described in any one of claims 1 to 6 or the low-temperature conductivity EPDM rubber material prepared by the preparation method as described in any one of claims 7 to 9 in the preparation of DC cable accessories.